Intra-Organ Variation in Age-Related Mutation Accumulation in the Mouse - Busuttil, Rita A. (Public Library of Science, 2007)
Using a transgenic mouse model harboring chromosomally integrated lacZ mutational target genes, we previously demonstrated that mutations accumulate with age much more rapidly in the small intestine than in the brain. Here it is shown that in the small intestine point mutations preferentially accumulate in epithelial cells of the mucosa scraped off the underlying serosa. The mucosal cells are the differentiated villus cells that have undergone multiple cell divisions. A smaller age-related increase, also involving genome rearrangements, was observed in the serosa, which consists mainly of the remaining crypts and non-dividing smooth muscle cells. In the brain we observed an accumulation of only point mutations in no other areas than hypothalamus and hippocampus. To directly test for cell division as the determining factor in the generation of point mutations we compared mutation induction between mitotically active and quiescent embryonic fibroblasts from the same lacZ mice, treated with either UV (a point mutagen) or hydrogen peroxide (a clastogen). The results indicate that while point mutations are highly replication-dependent, genome rearrangements are as easily induced in non-dividing cells as in mitotically active ones. This strongly suggests that the point mutations found to have accumulated in the mucosal part of the small intestine are the consequence of replication errors. The same is likely true for point mutations accumulating in hippocampus and hypothalamus of the brain since neurogenesis in these two areas continues throughout life. The observed intra-organ variation in mutation susceptibility as well as the variation in replication dependency of different types of mutations indicates the need to not only extend observations made on whole organs to their sub-structures but also take the type of mutations and mitotic activity of the cells into consideration. This should help elucidating the impact of genome instability and its consequences on aging and disease.